Synthesis and biological evaluation of histamine Schiff bases as carbonic anhydrase I, II, IV, VII, and IX activators - Suleyman Akocak; Nabih Lolak; Daniela Vullo; Mustafa Durgun; Claudiu T. Supuran (Taylor & Francis Group, 2017)
A series of 20 histamine Schiff base was synthesised by reaction of histamine, a well known carbonic anhydrase (CA, E.C 4.2.2.1.) activator pharmacophore, with substituted aldehydes. The obtained histamine Schiff bases were assayed as activators of five selected human (h) CA isozymes, the cytosolic hCA I, hCA II, and hCA VII, the membrane-anchored hCA IV and transmembrane hCA IX. Some of these compounds showed efficient activity (in the nanomolar range) against the cytosolic isoform hCA VII, which is a key CA enzyme involved in brain metabolism. Moderate activity was observed against hCA I and hCA IV (in the nanomolar to low micromolar range). The structure-activity relationship for activation of these isoforms with the new histamine Schiff bases is discussed in detail based on the nature of the aliphatic, aromatic, or heterocyclic moiety present in the aldehyde fragment of the molecule, which may participate in diverse interactions with amino acid residues at the entrance of the active site, where activators bind, and which is the most variable part among the different CA isoforms.